Health economic modeling for Alzheimer's disease: Expert perspectives. Issue 1 (26th October 2022) - Landeiro, Filipa; Morton, Jasmine; Gustavsson, Anders; Potashman, Michele; Lecomte, Pascal; Belger, Mark; Thompson, Robin; Roncancio‐Diaz, Emilse; Jhuti, Gurleen; Butler, Christopher; Jönsson, Linus; Handels, Ron; et al.
Abstract : Abstract: The successful development of an economic model for the evaluation of future Alzheimer's disease (AD) interventions is critical to accurately inform policy makers and payers. As our understanding of AD expands, this becomes an increasingly complex and challenging goal. Advances in diagnostic techniques for AD and the prospect of disease‐modifying treatments raise an urgent need to define specifications for future economic models and to ensure that the necessary data to populate them are available. This Perspective article provides expert opinions from health economists and governmental agency representatives on how future economic models for AD might be structured, validated, and reported. We aim to stimulate much‐needed discussion about the detailed specification of future health economic models for AD.